P786 Induction of endoscopic response, remission and ulcer-free endoscopy with upadacitinib is associated with improved clinical outcomes in patients with Crohn's disease. (30th January 2023) - Panés, J; Louis, E; Bossuyt, P; Joshi, N; Lee, W J; Lacerda, A; Remple, V; Xuan, S; Loftus Jr., E V
Abstract: Background: STRIDE-II guidelines recommend endoscopic healing as an important treatment goal in Crohn's disease (CD). This study evaluated the association of achieving endoscopic outcomes at week 12 and clinical outcomes at week 52 of maintenance treatment in patients with CD treated with upadacitinib (UPA). Methods: This post-hoc analysis evaluated data from two Phase 3 UPA induction (U-EXCEED and U-EXCEL) trials and the maintenance (U-ENDURE) trial in patients with moderate to severe CD. Patients who responded to 12-week induction therapy with UPA (45 mg per day [QD]) in U-EXCEED or U-EXCEL and received maintenance therapy with UPA (15 or 30 mg QD) up to 52 weeks in U-ENDURE were included. Clinical outcomes (CD activity index [CDAI] remission, CDAI response, steroid-free CDAI remission, high sensitivity C-reactive protein [hs-CRP] level ≤5 mg/L, and fecal calprotectin level [F-cal] ≤250 mcg/g), were evaluated at week 52 and compared between patients who achieved endoscopic response, endoscopic remission and ulcer-free endoscopy (absence of ulceration) at week 12 and those who did not using Chi-square test. Results: Of 337 clinical responders included in the analyses, 152 (45.1%), 87 (25.8%), and 75 (22.3%) patients achieved endoscopic response, endoscopic remission, and ulcer-free endoscopy, respectively, at the end of induction. Significantly more patients who achieved an endoscopic response at end of induction (vs those who did not) attained clinical outcomes at week 52 (CDAI remission, 52.0% vs 34.6%; CDAI response, 54.6% vs 39.5%; hsCRP ≤5 mg/L, 52.0% vs 30.8%; and F-cal ≤250 mcg/g, 42.1% vs 21.6%; P≤0.01, Table 1). Patients who achieved an endoscopic response vs those who did not at end of induction were also more likely to attain steroid-free CDAI remission (50.0% vs 30.9%) at week 52, (P≤0.05, Table 1). Similar findings were observed in patients who achieved endoscopic remission vs those who did not at end of induction (P≤0.01, Table 1). Significantly more patients attained CDAI remission (58.7% vs 37.7%), CDAI response (58.7% vs 42.7%), hsCRP ≤5 mg/L (58.7% vs 35.0%) and F-cal ≤250 mcg/g (50.7% vs 25.0%) at week 52, among patients who achieved ulcer-free endoscopy vs those who did not at end of induction (P≤0.05, Table 1). Conclusion: Achieving endoscopic outcomes at end of induction is associated with meaningful improvement in symptoms and inflammatory biomarkers at 52 weeks for patients with CD receiving UPA therapy. Endoscopic remission and ulcer-free endoscopy are associated with very similar long-term benefits.